Ombudsman Way : Jalan Menuju Perbaikan Pelayanan Publik - Meliala, Adrianus (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
As external oversight institution, Ombudsman Republic of Indonesia has 4 (four) unique and specific authorities. Besides undertaking mediation, conciliation and adjudication, delivery of recommendation/suggestion fulfill performance of Ombudsman Republic of Indonesia as endorsed by its law. This institution offers a non-legal and conflict-resolution mechanism pursuing solution to member of the public who do not satisfy with quality of public service delivered by whether central or local government. Key words: ombudsman, mediation, conciliation, adjudication, recommendation